STEENBEEK FOOT ABDUCTION BRACE FOR CLUBFOOT: COST EFFECTIVE BUT IS IT EFFECTIVE? A PROSPECTIVE STUDY - Dinesh, Thatikonda Sai; Kotian, Prem; PREMJIT SUJIR; VARGHESE JOE; RAJENDRA A (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Introduction: Foot Abduction Brace is recommended to prevent recurrence after casting phase in Ponseti method. Various types of braces are described, most current braces with proven efficacy are costly(100-300) and difficult to acquire especially for the common man in India. Steenbeek brace can be made with locally available materials and is very simple to make and is cost effective(10). Its efficacy is largely untested. Aim: To evaluate effectiveness of Steenbeek foot abduction brace to maintain correction achieved and to study the reasons for failure and complications associated with the brace. Materials and Methods: In KMC Mangalore and allied hospitals between Jun'2014-Aug'2016 25patients (38feet) who were treated by Ponseti method of cast application were given the Steenbeek foot abduction brace and followed up for a minimum duration of 1 year. The Status of foot was assessed using Pirani score before brace application and at every follow-up. Compliance with the brace protocol was assessed and Compliance defined as brace application for 23 hours/day for the first three months, and nap time brace application for rest of the duration of study. Results: In 36 of 38 feet on the brace the correction was maintained(94.7% effective). In two patients(feet) there was worsening of the Pirani score after brace application and recurrence was seen. The reason for failure was found to be non compliance. The correlation between noncompliance and recurrence was significant(p <0.001) using Fischer Exact Test. Pirani score improved significantly in compliant group with significant worsening noted in noncompliant group. There were no other brace related complications. Conclusions: The significant correlation between noncompliance and recurrence shows that Steenbeek FAB is effective in maintaining correction and can be a cost-effective alternative to the more costly braces, for use in developing countries.